The fiancée farce : a novel - Bellefleur, Alexandria (Avon, an imprint of HarperCollinsPublishers, 2023)
Running her family's bookstore while fending off questions about her love life, Tansy Adams invents a girlfriend, Gemma, inspired by the cover model on a bestselling book, but when the real-life Gemma--who needs to marry in order to inherit her family's publishing company--discovers Tansy's charade, she takes things one step further and announces their engagement.